On dimensioning the base of a traditional retaining wall. Issue 2 (9th May 2012) - Butterfield, R.
Abstract : When conventional retaining walls fail, they usually do so either by being transported bodily within a landslide of the material they are retaining or by a local failure of their foundation, particularly if it is a rigid base at shallow depth. The purpose of this letter is to present a rational way of determining the optimum geometry of such a base – for a specific wall height and relevant soil parameters – using a three-dimensional interaction diagram for a rigid base buried at shallow depth. The optimisation procedure required is novel because the loads acting on the base are a function of their dimensions. Furthermore, if the soil strength is scaled down, as in a 'limit state' design, the lateral load on the wall is increased whilst the load capacity of the base is decreased. The analysis presented provides a simple means of exploring the consequences of complex interactions of this kind. The methodology developed is independent of the method by which the resultant base loads ( V, H, M / B ) are decided and the analytical form of the failure locus.